"Jeg er kvinde" - Kroppen som baggrund i "Det andet køn" - Moi, Tori (Kvinder, Køn & Forskning, 1999)
The article discusses the possibilities of writing theory as a woman without neglecting the claims of the female body. Through a close reading of The Second Sex the author discusses the possibilities of situationg the body as either background or foreground depending on the situation of enunciation. Following Beauvoir's analyses the article concludes that while in some situations the fact of sex will be less important than the fact of class or race, in other situations it will not. The oppression of women consist in the compulsory foregrounding of the female body at all times, wether it is relevant or irrelevant to the task in the hand.